Upconversion 3D printed composite with multifunctional applications for tissue engineering and photodynamic therapy - Nigoghossian, Karina [UNESP]; Saska, Sybele [UNESP]; Christovam, Livia M. [UNESP]; Coelho, Fernanda [UNESP]; Beatrice, Cesar Augusto G.; Lucas, Alessandra A.; Neto, Paulo I.; da Silva, Jorge Vicente L.; Tercjak, Agnieszka; Baptista, Maurício S.; Catalani, Luiz Henrique; Scarel-Caminaga, Raquel M. [UNESP]; et al. (Sociedade Brasileira de Quimica (SBQ), 2020)
Upconversion nanoparticles (UCNPs) are suitable materials for bioapplications due to their ability to emit visible light under near infrared (NIR) excitation, in the biological transparency range. Polycaprolactone(PCL)-based scaffolds are widely used in tissue engineering in combination with inorganic compounds to improve bioactivity and osteoconductive properties. This work proposes a 3D printed composite scaffold with upconversion property aiming at biomedical applications in therapy-stimulated bone repair and photodynamic therapy (PDT). The system combines PCL polymer, UCNPs-apatite and a PDT photosensitizer. Thermal and rheological behaviors of the composite were similar to pure PCL polymer. Mechanical properties were improved by adding UCNPs-apatite. The 3D printable composite presented upconversion property and potential for PDT application, which was demonstrated by singlet oxygen generation under 980 nm excitation. Cytotoxicity, genotoxicity and mutagenicity assays indicated no toxicological effects at low concentrations of rare earth elements. Taken together, a potential multifunctional material is proposed for biomedical applications.
Keywords: 3D printing; Photodynamic therapy; Tissue engineering; Upconversion nanoparticles